Investigating Diagnostic Accuracy of Strip Kit (Rapid Test) for Detecting Aflatoxin M1 in Milk Based on the Concentration Obtained by ELISA and HPLC - Hanieh Amiri; Naser Morgan Azghadi; Azadeh Saki; Zeinab Rezaei; Ali Asghar Najafpoor; Mahsa Khakpour; Mansooreh Soltani (Journal of Nutrition and Food Security)
Background: The use of easy, fast, and accurate methods can be an important help in evaluating milk quality. The purpose of this study was to investigate the accuracy of diagnostic strip kits and compare it with ELISA and HPLC as a reference diagnostic method, which as the fastest diagnostic tool can play an important role in providing results. Methods: According to the catalog provided by the manufacturer, the samples were analyzed by rapid diagnostic kit and ELISA kit. Finally, the positive samples were checked by HPLC. Validation was done by comparing the results obtained from three methods as well as the values provided by the manufacturer. The limit of detection (LOD) was set at 100 ppt (ng/kg) and 50 ppt for Strip Kit and ELISA, respectively, and the limit of quantification (LOQ) was 5 ppt for confirmatory HPLC. Results: A total of 68 samples were selected to measure aflatoxin M1 (AFM1). Based on the results, 10 samples (14.7%) were positive by ELISA and 7 samples (10.29%) were detected to be positive by strip kit, of which only 3 (4.4%) samples were positive by reference method (HPLC). Moreover, among the strip kit test results, no sample was found as false-negative compared to HPLC, and the results of spike solution test with different concentrations also confirmed the results. The sensitivity and specificity of strip kit were calculated 70% and 100%, respectively. Conclusion: The strip kit can be used as a cheap, fast, and with acceptable accuracy method based on HPLC results for on-site detection of AFM1 in milk with saving time and money while guaranteeing high analytical precision and accuracy.